The learning curve for laparoscopic radical prostatectomy: an international multicenter study - Secin, Fernando P.; Rassweiler, Jens; Fiedler, Marcel (The journal of urology, 2010)
It is not yet possible to estimate the number of cases required for a beginner to become expert in laparoscopic radical prostatectomy. We estimated the learning curve of laparoscopic radical prostatectomy for positive surgical margins compared to a published learning curve for open radical prostatectomy.